Romanian Legal Structure of Agricultural Holdings in the Context of the Common Agricultural Policy 2014-2020 - BERCEAN, Radu Vlad (Journal of Legal Studies, 2015)
This Article "Legal structure of agricultural holdings romanian in the context of the common agricultural policy 2014-2020" falls within the field of agricultural research oriented structures, aiming to achieve a documentation of previous research, describe the existing situation and formulating its explanations.